Minds treating brains: understanding the interpretation of non-contrast CT ASPECTS in acute ischemic stroke. (1st February 2018) - Wilson, Alexis T.; Dey, Sadanand; Evans, James W.; Najm, Mohamed; Qiu, Wu; Menon, Bijoy K.
ABSTRACT: Introduction : The Alberta Stroke Program Early CT Score on non-contrast CT is a key component of prognostication and treatment selection in acute stroke care. Previous findings show that the reliability of this scale must be improved to maximize its clinical utility. Areas covered : This review discusses technical, patient-level, and reader-level sources of variability in ASPECTS reading; relevant concepts in the psychology of medical image perception; and potential interventions likely to improve inter- and intra-rater reliability. Expert commentary : Approaching variability in medical decision making from a psychological perspective will afford cognitively informed insights into the development of interventions and training techniques aimed at improving this issue.